A "tótoklakta Felföld" politikai földrajzi kérdései a dualizmus korabeli magyar földrajztudományban - Hajdú, Zoltán (Közép-Európai Közlemények, 2011)
The political structure of Historical Hungary was changed very deeply in 1867 with the Austrian-Hungarian Compromise. The modern Hungarian geography was established at the begining of 1870s. There were very strong connections between developments the political state and geography. The Hungarian political geographical researches were focusing on national problems of multinational and multiethnical Hungarian state. The Hungarian leading geographers (Hunfalvy János, Lóczy Lajos, Czirbusz Géza, Haltenberger Mihály) were not „nationalists” in their research works on Slovak problems. The Hungarian geographers without exception supported the state unity, against autonony movements.